2017
DOI: 10.1055/s-0042-121493
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids Inhibit Oxidative Stress and Inflammation in Mesangial Cells Induced by High Glucose and Lipopolysaccharide

Abstract: Recently, an connection between Short-chain fatty acids (SCFAs) produced by intestinal microbiota and kidney has been revealed. The aim of this study was to explore whether SCFAs or their specific G protein-coupled receptors 43 (GPR43) agonist inhibit oxidative stress and inflammatory response in glomerular mesangial cells (GMCs) induced by high glucose and lipopolysaccharide (LPS). Our research showed that treatment with SCFAs, especially acetate and butyrate, or GPR43 agonist significantly inhibited GMCs pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 21 publications
6
87
1
Order By: Relevance
“…Nevertheless, further research is required to elucidate the precise role of butyrate in the periodontal tissues under different in vitro conditions. Our research supports the role of butyrate to reduce ICAM-1 expression as observed in the intestine of burned rats [40], stimulated chondrocytes [41], glomerular mesangial cells [42], colon cancer cells [43], and endothelial cells [44]. These observations together with our findings are, however, in contrast to those showing that butyrate increases ICAM-1 in gingival carcinoma cells [23,45], leukemia cells [46] and endothelial cells [47,48].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, further research is required to elucidate the precise role of butyrate in the periodontal tissues under different in vitro conditions. Our research supports the role of butyrate to reduce ICAM-1 expression as observed in the intestine of burned rats [40], stimulated chondrocytes [41], glomerular mesangial cells [42], colon cancer cells [43], and endothelial cells [44]. These observations together with our findings are, however, in contrast to those showing that butyrate increases ICAM-1 in gingival carcinoma cells [23,45], leukemia cells [46] and endothelial cells [47,48].…”
Section: Discussionsupporting
confidence: 89%
“…However, with respect to the beneficial effects of butyrate on colitis [33,34], pathological bone loss [35], anti-microbial activity [36], and on a M1-to-M2 shift in macrophages [37-39] it should not be ruled out that SCFA may also contribute to tissue homeostasis by modulation of ICAM-1.Butyrate markedly reduces ICAM-1 expression in the intestine of severely burned rats [40] and in IL1β-stimulated chondrocytes [41]. Butyrate also reduces the expression of ICAM-1 in LPS-stimulated mouse glomerular mesangial and Caco-2 cells [42,43], and cytokine-induced ICAM-1 expression in cultured endothelial cells [44]. Conversely, other studies showed that butyrate increases ICAM-1 in human gingival carcinoma cell line 45], in acute myeloid leukemia cells [46] and endothelial cells [47,48].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present study has also shown that the expression of STRs and associated signaling components (Gα-gustducin, PLCβ2, and TRPM5) was rapidly downregulated upon exposure to glucose in a timeand dose-dependent manner in vitro. GMC proliferation and hypertrophy, ECM accumulation, as well as consequent renal fibrosis induced by high glucose, AGEs, or LPS, have been recognized as major pathogenic events in the progression of renal failure in DN [25]. Accordingly, our study found 30 mmol/L glucose stimulation for 24 h induced decrease of Ca 2+ after a certain lag period; meanwhile, NLRP3 inflammasome signaling molecules and inflammatory cytokine IL-1β release from GMCs were induced by high glucose, suggesting that STRs could be involved in the activation of NLRP3 inflammasome under high-glucose stress.…”
Section: Genementioning
confidence: 99%
“…There are numerous reports that showed beneficial effects of SCFAs in maintaining host immune function and intestinal barrier function; SCFAs serve as energy source for our body (in fact, our body has receptors for SCFAs) [8,9] , improve intestinal barrier function [10,11] , improve diabetes (through increasing production of incretin) [9,12] , inhibit allergic response (through improvement of regulatory T cell function) [13] , and scavenge oxygen radicals (by hydrogen produced in the process of SCFAs production) [14,15] . These functions may be more important when our body is exposed to a stressful condition such as that after a highly invasive abdominal surgery.…”
Section: Basic Knowledge Of Intestinal Microenvironmentmentioning
confidence: 99%